Some integral operators and their properties - Mustafa, Nizami (Kuwait Journal of Science, 2016)
In this study, some integral operators, which have broad applications in the theory of elementary particles and scattering, have been investigated in Holder space. We show that some important inequalities for the norm of these operators are also satisfied in Holder space.